ISOLATION, IDENTIFICATION AND BIOASSAY OF FLAVONOIDS FROM Bouea macrophylla GRIFF. - OTHMAN, ISNA ATHIRAH; AHMAT, NORIZAN; ADENAN, MOHD ILHAM; ZAHARI, ZURIATI; KAMAROZAMAN, AISYAH SALIHAH (Malaysian Applied Biology, 2022)
Bouea macrophylla Griff., a species belonging to the Anacardiaceae family is a flowering plant native to Southeast Asia and also known as kundang, kundang daun besar, and setar in Malaysia. The fruit can be eaten raw or as a pickle, while the young leaves can be consumed as salads. It has been claimed to be able to accelerate wound healing, prevent cancer, reduce the risk of stroke, and be good for blood circulation. The previous study on the plant from the same genus, known as B. oppositofolia has shown the presence of various. The present study was designed to isolate and elucidate flavonoids from this plant. The twig extract of kundang was purified by using several chromatographic techniques including Vacuum Liquid Chromatography (VLC), Column Chromatography (CC), and preparative-Thin Layer Chromatography (pTLC). The structures of isolated compounds were characterized by using spectroscopic methods including Nuclear Magnetic Resonance (NMR), infrared (IR), and ultraviolet (UV) spectral data, as well as comparison with the data reported in the literature. Five flavonoids were isolated and purified from the twigs of B. macrophylla which includes one flavanonol known as garbanzol; one flavonol which is resokaempferol; one flavandiol characterized as catechin; and two flavandiol known as mollisacacidin and guibourtacacidin. The results of the glucose uptake experiment indicated that the extract and compounds tested affected the glucose uptake rate of the insulin-resistant C2C12 cell line as compared to the standard. This is the first report describing the elucidation of the stated compounds from B. macrophylla as well as its glucose uptake study.